Pengaruh Citra Merek, Kualitas Produk dan Harga terhadap Keputusan Pembelian Smartphone Berbasis Android - Muhamad Ikhsan; Fajar Satria (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research examines and analyzes the influence of brand image, product quality, price simultaneously and partially on purchasing decisions. The research approach used in this research is quantitative research. This research uses a non- probability sampling technique using purposive sampling. The sample selection criteria in this study were people who had ever bought an Android smartphone, had used an Android smartphone, had used an Android smartphone for more than 1, year were >17 years old, were in the JABODETABEK area. The questionnaires collected were 150 respondents, the data was then processed using the multiple linear regression method. Based on the results of the analysis, it is known that partially the variables brand image, product quality and price have a positive effect on purchasing decisions. And the variables of brand image, product quality and price simultaneously have a positive effect on purchasing decisions.